Pengaruh Kecukupan Modal (CAR), Pertumbuhan Dana Pihak Ketiga (DPK), Kredit Bermasalah (NPL) terhadap Penyaluran Kredit Bank Umum Konvensional Yang Terdapat Dalam Bursa Efek Indonesia 2017–2021 - Adelina, Nina; Wagiyem, Wagiyem; Puspitasari, Andri Ani Ratna (STIE Atma Bhakti, 2024)
Credit distribution carried out by banks is one of the state's income sectors, which in this case is used to maintain economic stability, improve the level of social welfare, help develop MSMEs through loan capital provided by banks, therefore indirectly credit distribution is carried out by banks. is an effort to increase the level of welfare of citizens, the level of demand for credit has increased from year to year on the other bank's side, also considering CAR, DPK, NPL obtained from lending, there is a fear that banks will not be able to collect funds, excessive credit distribution will result in the risk of bad credit and widening which makes the bank lose balance. The population in this study was 46 banks. With this population, banking samples were taken using a purposive sampling method so that 26 banks were obtained that met the specified criteria. The type and source of data obtained from secondary data sources, the research method used is quantitative using multiple linear regression processed with the SPSS16 program. The results of multiple linear regression analysis and hypothesis testing can be concluded that simultaneously (F test) CAR, growth in deposits, NPL have an effect on banking credit distribution, while the results of partial analysis (T test) CAR, growth in deposits have no significant effect on credit distribution due to funds collected by the bank exceeds the reference provided by the IDX so that the bank has funds that are not distributed. It can be said that the amount of CAR, DPK has no influence on credit distribution, while for NPL it has a significant negative effect, which means that if credit distribution increases, the bank will experience an increase. NPL or bad credit, this problem causes banks to limit the distribution of credit funds in order to reduce the level of losses throughout the bank.